2016
DOI: 10.2174/0929867323666160615104837
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceuticals, A New Challenge for Medicinal Chemistry

Abstract: "Nutraceuticals" are food-derived products largely used for their presumed healthpromoting or disease-preventing effects. In the recent years, many efforts have been aimed at assessing nutraceutical efficacy and safety, but these factors are difficult to address because of the complex chemical compositions and multiple mode of actions. Thus, the study of nutraceutical ingredients poses several challenges for the medicinal chemistry field, some of which are related to extraction and chemical characterization, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 166 publications
1
43
0
1
Order By: Relevance
“…Considering the solubility properties nine NADES (2,3,4,10,11,17,28,29,30) were able to solubilize half of the rutin compared to the best solvent (ethanol). On the other hand, eutectic 11 and 28 (proline/glutamic acid 2:1 and proline/choline chloride 1:2 respectively) resulted to be the most promising NADES presenting rutin solubilization higher than ethanol and methanol.…”
Section: Pharmacokinetics In Mice Of Proline-glutamic Acid Rutin Eutementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the solubility properties nine NADES (2,3,4,10,11,17,28,29,30) were able to solubilize half of the rutin compared to the best solvent (ethanol). On the other hand, eutectic 11 and 28 (proline/glutamic acid 2:1 and proline/choline chloride 1:2 respectively) resulted to be the most promising NADES presenting rutin solubilization higher than ethanol and methanol.…”
Section: Pharmacokinetics In Mice Of Proline-glutamic Acid Rutin Eutementioning
confidence: 99%
“…Due to their safety level, the most commonly used solvents for nutraceutical production are water, ethanol or aqueous ethanol mixtures. Unfortunately, these mixtures may be scarcely efficient in extraction due to the variable nature and polarity of extractable bioactive compounds [1][2][3][4]. Additionally, many claimed active ingredients of nutraceuticals have poor bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of [M‐H] − ions together with low energy collision–induced dissociations occurring in the ion trap are suitable for tentative identification of triterpene acid constituents of apple. The analysis of triterpene composition of apple or other fruits can be a new opportunity for the development of functional foods, nutraceuticals, or food‐derived products with health‐promoting properties …”
Section: Introductionmentioning
confidence: 99%
“…Currently, studies on natural products and medicinal plants are one of the most important subjects in pharmaceutical area (Sut et al, 2016). In these studies, many plants or plant-derived products are suggested as potential agents for designing new pharmaceuticals or food ingredients (Raskin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%